At what size do anti-injury shelters start to play a positive role in the culture of Portunus trituberculatus? - He, Jie; Yu, Huaihua; Wan, Litao; Zhang, Dongxu; Xu, Wenjun (Frontiers in Marine Science, 2022)
Based on the existing research, special plastic baskets were used as anti-injury shelters to explore the hidden behavior and molting growth of Portunus trituberculatus（Swimming crab）different initial body weights (Group A: 5.74 ± 0.11 g, Group B: 12.06 ± 0.15 g, Group C: 24.82 ± 0.41 g, Group D: 49.55 ± 1.12 g and Group E: 94.32 ± 1.19 g). The results showed that the shelter occupancy rate (SOR) during the daytime with all different body weights was significantly higher than that at night (P < 0.05), and the SOR was proportional to the crab's body weight, among them, SOR in group E was as high as 71.52%. Meanwhile, the territorial consciousness of smaller body weight crabs (Groups A, B, and C) was poor, and there was a phenomenon in which multiple individuals occupied the same shelter at the same time, while the individuals with the body weight of approximately 50 g and above (Groups D and E) had strong territorial consciousness, and most of them occupied one shelter alone. In all groups, more individuals chose to molt in the shelter on condition that there existed shelter, and the rate of molting in group B was high up to 81.15%, and that in other groups was about 60%. Although the existence of shelter had no significant influence on the molting interphase (MI) of swimming crab in each group, the body weight growth rate (WGR) and carapace width growth rate (WGRC) after molting were increased by shelter compared with those without shelter. In addition, the shelter could improve the survival rate (SR) in each group, and the effect of shelter on individuals with large body weight was relatively more obvious, in which the SR in Group D was significantly improved (P < 0.05). In general, the shelter can play a positive role in the whole growth of swimming crab. Therefore, it is necessary to set up the shelter in advance before the seedlings are put into production, which is helpful to increase the yield of swimming crab.